PENGARUH MEDIA TERHADAP PRODUKTIVITAS CACING SUTERA (Tubifex sp) - Novi Sucipto; Zulkhasyni; Novita Hamron; Oktamalia Oktamalia; Hety Novitasari; Indra Indra Warman (Fakultas Pertanian, 2023)
Silk worms (Tubifex sp) is one of the natural feeds that are the main needs of larvae because they have more complete and complex nutrition compared to artificial feed. The existence in nature that is uncertain and very fluctuating makes silkworms difficult to obtain. To maintain its availability, it is necessary to conduct research and technological development in cultivation, especially finding out the type of culture media that is effective for reducing silkworms. Padang Jaya District, North Bengkulu Regency. This study aims to determine the best culture media composition to increase silkworm prodoktivity. This research was carried out at the Freshwater Aquaculture Development Center (BPBAT) of Bengkulu Province, Sido Luhur Village, Padang Jaya District, North Bengkulu Regency. In April – May 2019, using a Complete Randomized Design (RAL) consisting of 4 treatments and 4 repeats. Treatment A (pond mud 10%), B (pond mud 50% + chicken manure 20% + palm waste 30%), C (pond mud 50% + chicken manure 25% + palm oil waste 25%), D (pond mud 50% + chicken manure 30% + palm oil waste 20%). The variables observed during the study were absolute weight, organic matter content of the medium, water quality including temperature, and pH. The data was analyzed using fingerprint analysis and continued with the BNT test of 95% confidence level. The results showed that the influence of media on the productivity of silkworms (Tubifex sp) had a significantly different effect on the productivity of silkworms. It was concluded that treatment D is the media with the best composition to increase the productivity of silkworms with an absolute growth of 10.06 grams or 16.77%. The best C/N ratio was obtained by D media of 48.75.